Perspectives in HPV Secondary Screening and Personalized Therapy Basing on Our Understanding of HPV-Related Carcinogenesis Pathways - Aleksander Celewicz; Marta Celewicz; Michał Michalczyk; Rafał Rzepka (Mediators of Inflammation)
As cervical cancer is one of the most common malignancies in women worldwide even with present screening methods, the incidence in most developed countries is not decreasing for the last 15-20 years. A shift has been observed in the age of diagnosis in favour of younger women, and treatment of already developed cervical cancer is a challenge for surgeons. It is imperative to find new diagnostic methods for accurately pointing out patients at high risk of developing malignant disease and developing personalized treatment. Since cervical cancer is almost exclusively associated with HPV infection, understanding changes happening in an infected cell may prove invaluable for search of such methods, but it may also prove helpful in the diagnosis and treatment of other anogenital and nasopharyngeal region cancers. This review follows HPV-related changes in infected cell biology to point what potential markers and targets for therapy are in option when dealing with HPV-related diseases.